LITERASI DIGITAL BERBASIS SMART APPLICATION CREATOR (SAC): PENGUATAN PENDIDIKAN KARAKTER SISWA MADRASAH IBTIDAIYAH DI ERA SOCIETY 5.0 - Fauziyah, Litsa Nailul; Muhith, Abd; Sutomo, Moh; Uswah, Atiq Yufitria (JPGMI (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Multazam), 2023)
This research is a qualitative study with a type of library research. The purpose of this study is to describe and analyze the advantages and disadvantages of Digital Literacy based on Smart Application Creator (SAC) in Strengthening Character Education for Madrasah Ibtidaiyah Students in the Era of Society 5.0. Data collection techniques using documentation sourced from scopus articles, accredited journal articles, international proceedings, Google Scholar journals, and scientific books, were searched by searching for keywords: digital literacy, Smart Application Creator (SAC), character education, era society 5.0. The journals selected were those that were related to the keywords. After the data was collected, it was analyzed using descriptive analysis and content analysis. The results showed that the use of digital literacy based on Smart Application Creator (SAC) proved effective for strengthening the character education of Madrasah Ibtidaiyah students. And can be offered as an alternative in the world of education to face the era of society 5.0 because access to learning is facilitated through digital technology or Information and Communication Technology (ICT).